A responsabilidade social corporativa reduz o risco das firmas? evidências de setores industriais controversos brasileiros - Larissa Queiroz de Melo (2020)
The present study aimed to identify a relationship between risk and to adopt corporate social The present study aimed to identify the relationship between risk and the adoption of corporate social responsibility practices by firms, highlighting firms belonging to controversial sectors. To this end, it used a sample made up of publicly traded Brazilian companies that were listed on B3 from 2010 to 2018. The risk of Brazilian companies was measured based on four proxies, namely: total risk, market risk , specific risk, and market ranking risk. The performance of firms with regard to social responsibility was measured by five proxies, a categorical variable that signals the listing of the company over the period analyzed in the Company Sustainability Index (ISE) and a variable relative to the average aggregate of the firm in performance in CSR. In addition, the latter was used disaggregated in the environmental, social and governance dimensions. In relation to the statistical method used, multiple regressions were used with the dynamic panel data approach estimated by GMM. The results found reveal that, for the analyzed sample, the adoption of CSR practices related to social aspects (community, product responsibility, workforce and human rights) and governance (relations with shareholders, management, shareholders and CSR strategies ) reduces the firms' total risk. However, when analyzed for controversial sectors, the results indicate a positive relationship in relation to market risk, based on the general dimension of CSR and the social dimension. These findings suggest that, belonging to a controversial sector and adopting CSR practices, has a positive effect on risk. Explanations for this relationship are supported by the window-dressing hypothesis, according to which the market may consider the adoption of CSR practices by controversial firms as a facade mechanism, used to cover up the true impact of their activities. in the environment in which they operate.